Electroanalytical Overview: Screen‐Printed Electrochemical Sensing Platforms - Robert D. Crapnell; Craig E. Banks (ChemElectroChem, 2024)
Abstract Screen‐printed electrochemical sensing platforms are ubiquitous within the field of electrochemistry where they provide benefits of being disposable, cost‐effective, reproducible, easily customisable, portable and allow one to transfer the laboratory approach into the field. In this review, we introduce the concept of screen‐printed electrodes, we summarise positive and negative aspects before moving into the current highlights of using traditional screen‐printed carbon electrodes within the field of electroanalysis. We then look to cover metallic and bulk modified varieties, geometric changes (micro, microband and associated arrays), electrode activation and finally the physical length of screen‐printed electrodes, providing insights for future research.